2015
DOI: 10.1158/1538-7445.am2015-5593
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5593: Cigarette smoke and therapeutic response to chemotherapy and radiotherapy in cancer cells

Abstract: Background: The 2014 Surgeon General's Report concludes that cigarette smoke (CS) causes increased cancer specific mortality. Clinical data support that the effects of CS are reversible, but there are no extant biologic models that have shown therapeutic response profiles for cancer cells exposed to CS. Methods: An acute, subacute, and chronic dose escalated CS exposure model was developed to test the hypothesis that CS decreases therapeutic response to chemotherapy (CT, cisplatin) and radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 6 From a preclinical perspective, it was observed that cigarette smoking was associated with therapeutic response to chemotherapy and radiotherapy in cancer cells. 7 Interestingly, evidence revealed that smoking may induce the epithelial-to-mesenchymal transition in lung cancer cell lines. 8 In the clinical practice, several trials reported that smoking status affected the survival of NSCLC patients in the treatment with anti-PD-1 agents.…”
Section: Introductionmentioning
confidence: 99%
“… 6 From a preclinical perspective, it was observed that cigarette smoking was associated with therapeutic response to chemotherapy and radiotherapy in cancer cells. 7 Interestingly, evidence revealed that smoking may induce the epithelial-to-mesenchymal transition in lung cancer cell lines. 8 In the clinical practice, several trials reported that smoking status affected the survival of NSCLC patients in the treatment with anti-PD-1 agents.…”
Section: Introductionmentioning
confidence: 99%